PENGEMBANGAN POTENSI KAMPUNG WISATA TERPADU, KAMPUNG HIJRAH, PANUNGGANGAN UTARA - Andreas Kiky; Gillian Emery Chandra; Anastasia Melia Ciptadi; Devanya Azzura Andisi Salim; Jessica Angelina (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
Community development in Kampung Hijrah aims to map this region's potency as integrated tourism and economic activity for villagers. Initially, Kampung Hijrah had a negative reputation that needed to be rebranded by RT and teach the villagers to create their own economic activity. The development of eco-tourism in Kampung Hijrah started with the inauguration of a fishing recreation spot during this program. This fishing spot could create a recreation place that has valuable economic transactions. However, future evaluation and monitoring are crucial to the following programs. The improvement in understanding of good corporate governance in managing the business and good resources (capital) allocation are two critical success factors before the venture could bring social welfare for the nearby villagers.